Sequence of b cytochromes relative to ubiquinone in the electron transport chain of Escherichia coli. - Downie, J A (1978)
A ubiquinone-deficient mutant, carrying mutations in two genes affecting ubiquinone biosynthesis, has been used, in comparison with a normal strain, to determine the sequence of some of the components of the electron transport chain of Escherichia coli. The amounts of cytochromes reduced during aerobic steady-state conditions were estimated by comparing low-temperature difference spectra of normal or ubiquinone-deficient membranes with either D-lactate or reduced nicotinamide adenine dinucleotide as substrate. From the amounts of cytochromes reduced it was concluded that ubiquinone functions at two sites, one site being between the dehydrogenases and cytochromes and the second site being after cytochromes b562 and b556 but before cytochromes b558, d, and o. The scheme proposed is discussed in relation to the Mitchell protonmotive ubiquinone cycle.